KAJIAN TEKNIS PEWARNAAN BATIK DENGAN PEWARNA ALAMI DI KAMPUNG ALAM MALON GUNUNG PATI KOTA SEMARANG - Damayanti, Ariyana; Haq, Arina (Universitas Negeri Surabaya, 2025)
The purpose of the study was to determine the natural coloring technique in the batik making process in Kampung Alam Malon, Gunung Pati District, Semarang City. Kampung Batik Alam Malon with its natural conditions is still pristine, there are many natural plants that can be used to make dyes, including indigo trees, jelawe trees, tall trees and so on. The research method in this study is descriptive exploratory. Data search will be carried out by means of literature studies, observations, observations, and interviews. Batik textile coloring takes a long time and a long process, starting from the preparation of textile materials with mordant, the waxing process, the first coloring at least 5 times of dipping, drying for 5 times, fixaxi with various solutions such as tunjung, lime and alum, from this fixaxi process natural dyes can be varied into various desired color choices. Natural dyes from jelawe produce yellow, indigovera produces blue and tall produces brown.